2018
DOI: 10.3390/inorganics6030096
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Synthesis of Pillared-Layered Magnesium Tetraphosphonate Coordination Polymers: Framework Interconversions and Proton Conductivity Studies

Abstract: Novel pillared-layered framework materials were synthesized by high-throughput or microwave-assisted methodology that contain Mg2+ and the zwitterionic linker HDTMP (hexamethylenediamine-N,N,N′,N′-tetrakis(methylenephosphonic acid)). Three compounds were structurally characterized by X-ray powder diffraction. In the compound {Mg[(HO3PCH2)2N(CH2)6N(CH2PO3H2)2]·(H2O)}n(1), obtained at 140 °C by hydrothermal or microwave-assisted reaction, the layers are built by isolated Mg2+ octahedra coordinated by oxygen atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Metal phosphonates represent a rich area of coordination and materials chemistry that has seen impressive growth in the last few decades due to their multiple properties as proton conductors, , scale and corrosion inhibitors, catalysts, , and as platforms for pharmaceutical drug delivery, , among others. By combining (poly)­phosphonic acid linkers , and a variety of synthetic methodologies, including mechanochemical , and high-throughput , procedures, numerous metal phosphonates have been prepared for targeted applications, as they are amenable to establish appropriate structure/property relationships, assisted by advanced characterization techniques, such as synchrotron radiation or electron diffraction tomography …”
Section: Introductionmentioning
confidence: 99%
“…Metal phosphonates represent a rich area of coordination and materials chemistry that has seen impressive growth in the last few decades due to their multiple properties as proton conductors, , scale and corrosion inhibitors, catalysts, , and as platforms for pharmaceutical drug delivery, , among others. By combining (poly)­phosphonic acid linkers , and a variety of synthetic methodologies, including mechanochemical , and high-throughput , procedures, numerous metal phosphonates have been prepared for targeted applications, as they are amenable to establish appropriate structure/property relationships, assisted by advanced characterization techniques, such as synchrotron radiation or electron diffraction tomography …”
Section: Introductionmentioning
confidence: 99%
“…Among the assorted reasons why there are so many reports in the area of MOFs and PCPs, and why they remain an attractive topic of research, one can point out their tunable chemical structure and/or their multifunctional properties [2]. The ability to design a network with specific pore sizes and shapes is one of the main features why these materials are good candidates for multiple applications in different research areas like gas storage and separation [3,4], catalysis [5,6], sensing [7][8][9][10][11], and drug delivery [12,13], among others [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…9 Cabeza et al 10 also have reported the crystalline structure of Ca 2+ -phosphonate using 5-(dihydroxyphosphoryl)isophthalic acid, which has −COOH as protogenic groups exhibiting good proton conductivity in range of magnitude of 10 –3 S·cm –1 . The authors 11 also have reported the solvothermal synthesis of Mg 2+ -phosphonate using hexamethylenediamine-tetra(methylenephosphonic acid), which shows remarkable proton conductivity (in the range of ∼10 –5 S·cm –1 ) because of having P–OH and −NH + groups as proton sources. Ploehn et al 12 have prepared polymer composite materials using a combination of mixed metals and phenylphosphonic acid (M = Mg, Ca, Sr, and Pb) and explored its dielectric permittivity, which was found to be higher than its parent composite material.…”
Section: Introductionmentioning
confidence: 99%